Transient optical absorption in calcium fluoride crystals - Stepanov, S. A.; Chinkov, E.; Shrayber, A. M.; Shtanko, V. (Radiation physics and chemistry)
We report time-resolved measurements of transient optical absorption and emission in nominally pure CaF2 crystal. For excitation we used a pulse of accelerated electrons. It was shown that irradiation leads to the formation of centers of induced absorption, which are deconvoluted by the set of Gaussian bands with maxima at 2.70, 2.91, 3.09, 3.30 eV (F centers) and 3.825, 4.03, 4.30, 4.83 eV (H centers). Four possible geometries of the STE in the fluorite lattice are shown. Assumptions are made about the conversion of configurations.